Integrability and $L^1$-Convergence of Double Cosine Trigonometric Series (Analysis in Theory and Applications, 2018)
We study here $L^1$-convergence of new modified double cosine trigonometric sum and obtain a new necessary and sufficient condition for $L^1$-convergence of double cosine trigonometric series. Also, the results obtained by Moricz[1],[2] are particular cases of ours.